Effectiveness Of Oxytocin Massage On Weight Gain Of Infants With Growth Delay Among Breastfeeding Mothers In The Working Area Of UPTD Puskesmas Kalapanunggal In 2025 - Diana Damayanty; Lisa Trina Arlym; Rukmaini (Rajaki of Tulip Medika Publisher, 2025)
Abstract Background: Infant weight gain is an important indicator of nutritional and health status. One method to improve weight gain is oxytocin massage, which stimulates breast milk production. In the working area of UPTD Kalapanunggal Public Health Center, cases of infants with slow growth are still found, requiring effective interventions. Objective: This study aimed to determine the effectiveness of oxytocin massage on weight gain in infants with slow growth in the working area of UPTD Kalapanunggal Public Health Center. Methods: This study used a quasi-experimental design with a pre- and post-test with control group approach. The sample consisted of 30 breastfeeding mothers, divided into a control group (milk supplementation only) and an intervention group (milk supplementation + oxytocin massage). The instruments used were a digital scale, an infant weight observation sheet, and an oxytocin massage SOP. Data were analyzed using the Wilcoxon test to examine differences before and after the intervention in each group, and the Mann–Whitney test to compare the two groups. Results: The Wilcoxon test showed a significant difference in infant weight gain before and after the intervention in both groups (p<0.05). The Mann–Whitney test indicated that infant weight gain in the intervention group was higher than in the control group (p<0.05). Conclusion: Oxytocin massage is effective in increasing weight gain in infants with slow growth. Recommendation: Health workers are encouraged to apply oxytocin massage as a supporting intervention to improve infant growth in health facilities.